Grid Synchronization of the VSC-HVDC System Based on Virtual Synchronous Generator Control Strategy - M. Chethan; Ravi Kuppan (International Transactions on Electrical Energy Systems)
This paper explores an integration of virtual synchronous generators into voltage source converter–based VSC-HVDC systems to enhance grid stability and performance. VSGs emulate the inertia and damping characteristics of traditional synchronous generators, thereby providing essential frequency support and improving transient stability during disturbances. The study focuses on design considerations, control strategies, and the impact of VSG incorporation on system dynamics. Through detailed simulations and analyses, it is demonstrated that VSGs can significantly reduce the rate of change of frequency during transient events, thus enhancing the overall robustness and reliability of VSC-HVDC systems. In addition, the practical challenges of implementing VSG-based control are addressed, and solutions are proposed to optimize system integration and performance.